An adaptive protection coordination scheme for microgrids with optimum PV resources. (15th March 2022) - Dorosti, Peiman; Moazzami, Majid; Fani, Bahador; Siano, Pierluigi
Abstract: Nowadays, microgrids provide several economic and environmental benefits for customers, investors, and power networks. Their practical implementation, however, has several technical challenges such as energy management, control, and protection. The protection coordination is a crucial problem in microgrids with high penetration of renewable-based distributed generations such as photovoltaic units. In previous studies, despite the network's need for maximum photovoltaic resources, the installed capacity of these resources was assumed to be constant and limited due to the miscoordination of protective devices as a result of increasing network short-circuit level. This paper presents an optimal adaptive protection coordination scheme in microgrids with optimum penetration levels of photovoltaic resources without dependency on communication infrastructures, such as ways of communication between relays and central control room for analyzing all relay signals depends on fault condition and changing the setting step in adaptive relays. The proposed methodology can generally increase the penetration level of photovoltaic resources while minimizing the generation costs of photovoltaic resources by optimizing the installation capacity of each bus. The proposed adaptive protection coordination is achieved without changing the settings of existing protective devices. The optimal capacity of photovoltaic resources is updated through optimization algorithms such as non-dominate storing genetic algorithm considering several constraints including loss and cost minimization and voltage limits. Highlights: An adaptive protection coordination with optimal penetration of PV resources. Increasing PV penetration while minimizing the PV costs and power losses. Unrequiring communication infrastructures and re-adjusting protective devices. Determining the capacity of each PV resource according to fault condition dynamically.